Promoting Students’ interest in English speaking lessons by using Group work for 11th grade at Duong Tu Minh High School - Nông, Thị Thanh Huyền (University of Languages and International Studies, 2017)
This thesis was carried out to investigate the benefits of using group work in English speaking lessons. It sought the answers to the following hypothesis: ‘Group work does promote students’ interest in English speaking lessons to students ‘ The researcher (...)